2016
DOI: 10.18632/oncotarget.8624
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-rich Avicennia marina leaf extracts induce apoptosis in human breast and liver cancer cells and in a nude mouse xenograft model

Abstract: Avicennia marina is the most abundant and common mangrove species and has been used as a traditional medicine for skin diseases, rheumatism, ulcers, and smallpox. However, its anticancer activities and polyphenol contents remain poorly characterized. Thus, here we investigated anticancer activities of secondary A. marina metabolites that were purified by sequential soxhlet extraction in water, ethanol, methanol, and ethyl acetate (EtOAc). Experiments were performed in three human breast cancer cell lines (AU56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
4
19
4
3
Order By: Relevance
“…Apoptosis is a physiological process that eliminates abnormal or nonfunctional cells and is critical for maintenance of tissue homeostasis, and failure of apoptosis results in accumulation of abnormal cells, potentially leading to tumor development [ 42 ]. Cell apoptosis is regulated at multiple levels and involves anti-apoptotic protein Bcl-2 and pro-apoptotic protein Bax.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a physiological process that eliminates abnormal or nonfunctional cells and is critical for maintenance of tissue homeostasis, and failure of apoptosis results in accumulation of abnormal cells, potentially leading to tumor development [ 42 ]. Cell apoptosis is regulated at multiple levels and involves anti-apoptotic protein Bcl-2 and pro-apoptotic protein Bax.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple treatments have been developed for breast cancer, such as local surgical treatment, radiotherapy and chemotherapy, endocrine therapy, molecular targeted treatment, auxiliary treatment of traditional Chinese medicine and so on, which significantly improves the quality of life and prolongs the survival period of patients ( 7 11 ). A large number of clinical data and experimental studies have shown that the adjuvant treatment of breast cancer patients with traditional Chinese medicine can improve the body's metabolism, reduce the toxic and side effects of radiotherapy and chemotherapy, improve the surgical resection rate and endocrine therapy efficacy, and so on ( 12 , 13 ). The development of traditional Chinese medicine plays an important role in reducing the recurrence and metastasis of tumor, prolonging the survival time, and improving the quality of patients' life ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Avicennia marina possess various pharmacological and bioactive activities including anticancer [17][18][19], antimalarial [20][21][22], anti-inflammatory [23][24], antiviral [25][26], antioxidant [27][28][29], antibacterial [20][21][22][23][24][25][26][27][28][29][30][31][32], antifungal [33][34][35], herbal immunostimulant [36] and various protective effects [37] etc., made this mangrove a traceable source for already exist phytochemicals as well as new drug discovery in herbal treatment systems for various disease prevention. Apart from their plentiful uses in several disease treatments and ethnomedicinal worth and practicality, the chromatographies HPTLC pattern analysis or optimized fingerprint of Avicennia marina leaf, stem and root has not been fully reported yet and still very little is known related to whole Phytochemistry of its different plant parts.…”
Section: Introductionmentioning
confidence: 99%